The origins of cocaine
1 online resource (190 pages)
Keywords: In the 1960s, the governments of Colombia, Peru, and Bolivia launched agricultural settlement programs in each country’s vast Amazonian frontier lowlands. Two decades later, these exact same zones had transformed into the centers of the illicit cocaine boom of the Americas. Drawing on concepts from both history and anthropology, The Origins of Cocaine explores how three countries with divergent different mid-century political trajectories ended up with parallel outcomes in illicit frontier economies and cocalero cultures. Bringing together transnational, national, and local analyses, the volume provides an in-depth examination of the deep origins of drug economics in the Americas. As the first substantial study on the shift from agrarian colonization to narcotization, The Origins of Cocaine will appeal to scholars and postgraduate students of Latin American history, anthropology, globalization, development and environmental studies.